2007
DOI: 10.1002/ijc.23090
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of IFN‐γR in association with loss of Fas function is linked to tumor progression

Abstract: The host immune system functions as an intrinsic surveillance network in the recognition and destruction of tumor cells, and it has been demonstrated that lymphocytes and IFN-c are the primary tumor suppressors of the immune system. However, the immune system can concurrently select for tumor variants with reduced immunogenicity and aggressive phenotypes. We report here that tumor escape variants that have survived CTL adoptive immunotherapy exhibited decreased expression levels of both Fas and IFN-cR in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 63 publications
0
29
0
Order By: Relevance
“…Previous studies have demonstrated that Fas is highly expressed in normal colorectal epithelial cells, whilst a loss of Fas expression and anti-Fas-mediated apoptosis in colorectal cancer cells contributed to tumor invasion and metastasis (6,7,19). The present study indicated that the expression of Fas reduced significantly as the malignancy of the epithelial cells increased (P=0.0271).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that Fas is highly expressed in normal colorectal epithelial cells, whilst a loss of Fas expression and anti-Fas-mediated apoptosis in colorectal cancer cells contributed to tumor invasion and metastasis (6,7,19). The present study indicated that the expression of Fas reduced significantly as the malignancy of the epithelial cells increased (P=0.0271).…”
Section: Discussionmentioning
confidence: 99%
“…IFNg expression is also essential for CD8-mediated antitumor activity. This effect can be partially explained by the capacity of IFNg to induce Fas on dysplastic target cells surface thus inducing cell death by Fas ligand-Fas interaction (35,36). Moreover, IFNg increases the expression of MHC class I expression on target cells thus promoting recognition of tumor-associated antigens (37).…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking sensitivity to IFNg, such as IFNg receptor-deficient mice, developed tumors more rapidly and with greater frequency than IFNg-sensitive mice (25). Tumor escape variants that survive CTL adoptive immunotherapy exhibit decreased expression levels of the IFNg receptor (26). In humans, IFNg receptor a expression is lower in cases of infiltrating breast cancer than in cases of in situ tumors (27).…”
Section: A Possible Mechanism Underlying the Controversial Effects Ofmentioning
confidence: 99%